Pediatric Septic Arthritis of the Knee Due to a Multi-Sensitive Streptococcus pyogenes Strain Responsive to Clindamycin-A Case Report - Giada Maria Di Pietro; Irene Maria Borzani; Sebastiano Aleo; Samantha Bosis; Paola Marchisio; Claudia Tagliabue (MDPI AG, 2021)
Septic arthritis is an inflammatory process usually generated by a bacterial infection. The knee is one of the most frequently involved joints. The etiology varies depending on age, and hematogenous spread remains the primary cause in children. Herein, we report a case of a previously healthy three-year-old female who was referred to our institution for acute swelling of her right knee. After a clinical and radiological diagnosis of septic arthritis, an empirical treatment with a combination of cefotaxime and clindamycin was initiated. The isolation of a multi-sensitive Streptococcus pyogenes strain from the joint's effusion prompted the discontinuation of clindamycin and the usage of cefotaxime alone. One week later, an ultrasound was executed due to worsening in the patient's clinical conditions, and an organized corpuscular intra-articular effusion with diffuse synovial thickening was revealed. Cefotaxime was therefore replaced with clindamycin, which improved the symptoms. Despite the antibiotic sensitivity test having revealed a microorganism with sensitivity to both cephalosporin and clindamycin, clinical resistance to cefotaxime was encountered and a shift in the antimicrobial treatment was necessary to ensure a full recovery. This case study confirms that an antibiotic regimen based solely on a susceptibility test may be ineffective for such cases.